Transfers, nutrition programming, and economic well-being: Experimental evidence from Bangladesh - Ahmed, Akhter; Hoddinott, John F.; Roy, Shalini; Sraboni, Esha (Elsevier, 2024)
Many cash transfer programs include complementary nutrition training, with the aim of encouraging households to use transfer resources toward improving child nutrition. Evidence indicates that these bundled programs, if intensive and well-implemented, can be effective in improving child nutritional status. However, little is known about how adding nutrition training to transfer programs affects their economic impacts. In particular, few studies have assessed whether nutrition programming may induce reallocation of transfer resources from physical capital to human capital. Scarce evidence also exists as to whether these tradeoffs depend on the transfer modality. We study a pilot program called the Transfer Modality Research Initiative in Bangladesh (TMRI), designed as a randomized controlled trial. TMRI provided cash or food transfers, with or without intensive group-based nutrition behavior change communication (BCC), to mothers of young children in poor rural households. We find that adding nutrition BCC to cash or food transfers leads to larger impacts on both consumption and assets – potentially surprising, given that the transfer value is unchanged. Analysis of mechanisms suggests that these effects occur through the BCC inducing increases in income generation, through investments in livelihoods. Suggestive evidence indicates that the effects of TMRI’s BCC are plausibly due to the intensive group-based format, which increased social capital for participant women and their household members, as well as improved participant women’s agency and self-confidence, knowledge, and input into household decisions. Results indicate that adding nutrition BCC to cash or food transfer programs do not necessarily induce a tradeoff between investing in human capital versus physical capital, but can rather strengthen impacts on both if appropriately designed.